2022
DOI: 10.1021/acs.inorgchem.1c03988
|View full text |Cite
|
Sign up to set email alerts
|

Linker Deprotonation and Structural Evolution on the Pathway to MOF-74

Abstract: The synthesis of MOF-74 (MOF = metal−organic framework) proceeds first through the generation of chemically and topologically distinct materials, referred to as phases, displaying exclusively carboxylate coordination, followed by further deprotonation to enable oxo coordination and MOF-74 formation. The synthesis of Mg-MOF-74 at high concentrations of linker and metal enables the stabilization and characterization of the previously unobserved, exclusively carboxylate coordinating phases. Ex situ and in situ ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 34 publications
4
41
0
Order By: Relevance
“…Unfortunately, higher reaction concentrations (>0.1 M) led to impure materials (not shown), limiting the scalability of this solvothermal method. 26 Having optimized the solvothermal synthesis of Mg 2 (mdobdc), we set out to improve the mechanochemical synthesis of this material for comparison. Previously, we reported the mechanochemical synthesis of Mg 2 (dobdc) using N,N-diisopropylethylamine (Hünig's base) as both the base required to deprotonate the linker precursor and as the liquid to facilitate liquid-assisted grinding in a planetary ball mill.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, higher reaction concentrations (>0.1 M) led to impure materials (not shown), limiting the scalability of this solvothermal method. 26 Having optimized the solvothermal synthesis of Mg 2 (mdobdc), we set out to improve the mechanochemical synthesis of this material for comparison. Previously, we reported the mechanochemical synthesis of Mg 2 (dobdc) using N,N-diisopropylethylamine (Hünig's base) as both the base required to deprotonate the linker precursor and as the liquid to facilitate liquid-assisted grinding in a planetary ball mill.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, higher reaction concentrations (>0.1 M) led to impure materials (not shown), limiting the scalability of this solvothermal method. 26…”
Section: Resultsmentioning
confidence: 99%
“…New phases form in the 5× concentration synthesis including a spherical material (Figure c and Figure S24 for the bulk distribution). It has been shown that, at high concentration, multiple phases can be stabilized over the course of a Mg-MOF-74 synthesis, and the increased variability related to the expression of multiple phases is magnified by the stochastic nature of crystal nucleation . Seeding the synthesis of Mg-MOF-74 enables enhanced phase selection as evidenced by PXRD and SEM, which shows reduced expression of off-target phases (Figure a and Figure S25).…”
mentioning
confidence: 99%
“…Industry routinely employs seeding to control the kinetics of crystallization and drive phase selection. At high concentrations of metal and linker, it is possible to dramatically improve both throughput and the ratio of MOF generated to solvent used; however, these conditions also cause normally phase pure MOF syntheses to break down, 15 generating offtarget phases, increasing defect concentration, and potentially producing amorphous content, all resulting in reduced yield and/or product quality. This erosion in phase purity most often manifests as a reduction in surface area of the targeted MOF and the appearance of additional phases in the PXRD pattern.…”
mentioning
confidence: 99%
“…Unfortunately, higher reaction concentrations (>0.1 M) led to impure materials (not shown), limiting the scalability of this solvothermal method. 26 Having optimized the solvothermal synthesis of Mg2(mdobdc), we set out to improve the mechanochemical synthesis of this material for comparison. Previously, we reported the mechanochemical synthesis of Mg2(dobdc) using N,Ndiisopropylethylamine (Hünig's base) as both the base required to deprotonate the linker precursor and as the liquid to facilitate liquid-assisted grinding in a planetary ball mill.…”
Section: Resultsmentioning
confidence: 99%